Determinants of seropositivity among HPV-16/18 DNA positive young women - Porras Carolina; Bennett Christina; Safaeian Mahboobeh; Coseo Sarah; Rodríguez Ana Cecilia; González Paula; Hutchinson Martha; Jiménez Silvia; Sherman Mark E; Wacholder Sholom; Solomon Diane; van Doorn Leen-Jan; et al. (BMC Infectious Diseases, 2010)
Abstract Background Not all women infected with HPV-16/18 have detectable levels of HPV-16/18 antibodies, those who seroconvert develop low antibody levels, and seroconversion occurs typically several months post-infection. We evaluated determinants of seropositivity among 646 women infected with HPV-16 and/or HPV-18. Methods Data are from the enrollment visit of the NCI-sponsored Costa Rica HPV Vaccine Trial. Sera were tested for HPV-16/18 antibodies by ELISA; cervical specimens were tested for HPV DNA using HC2 and SPF10/LiPA25. Odds ratios (OR) and 95% confidence intervals (CI) were computed. Results Among HPV-16/18 DNA positives, seropositivity was 63.0% and 57.5%, respectively. Among HPV-16 DNA positives, seropositivity increased with lifetime number of sexual partners (p-trend = 0.01). Women with abnormal cytology and/or high viral load had a 1.63-2.79-fold increase in the detection of antibodies compared to women with normal cytology/low viral load. Current users of oral contraceptives had a 1.88-fold (95%CI, 1.14-3.09) increased detection of antibodies and current users of injectables had a 3.38-fold (95%CI, 1.39-8.23) increased detection compared to never users. Among HPV-18 DNA positive women, seropositivity was associated with current oral contraceptive use (OR 2.47; 95%CI 1.08-5.65). Conclusions Factors associated with sustained HPV exposure (abnormal cytology, elevated HPV viral load, increasing lifetime partners) were predictive of HPV-16 seropositivity. Hormonal contraceptive use was associated with seropositivity suggesting an effect of hormones on immune responses to HPV. Patterns were less consistent for HPV-18. Follow up of incident HPV infections to evaluate seroconversion and their determinants is needed.